Predictors for early readmission in patients hospitalized with new onset pediatric lupus nephritis. (October 2021) - AH Guerra, Angel; Garro, Rouba; McCracken, Courtney; Rouster-Stevens, Kelly; Prahalad, Sampath
Objective: The objective is to determine the 30-day hospital readmission rate following a hospitalization due to pediatric lupus nephritis of recent onset and characterize the risk factors associated with these early readmissions. Methods: The study included 76 children hospitalized from 01/01/2008 to 4/30/2017 due to a new diagnosis of lupus nephritis. We calculated the 30-day hospital readmission rate and compared the characteristics of the patients that were readmitted to patients that were not readmitted using univariable and multivariable analysis. Results: The 30-day readmission rate was 17.1%. Factors that predicted hospital readmission in unavailable analysis were male gender (38.5 vs 14.3%, p = 0.04), not receiving pulse steroids (30.8 vs 3.2%, p = < .001), receiving diuretic treatment (69.2 vs 34.9%, p = .02), receiving albumin infusions (46.2 vs 12.7%, p = .004), stage 2 hypertension on day one of admission (76.9 vs 41.3%, p = .02), a higher white blood cell count on discharge (13.7 × 10 3 /mm 3 vs 8.8 × 10 3 /mm3, p = .023), need for non-angiotensin converting enzyme (ACE) antihypertensive drugs (76.9 vs 46%, p = .042), and being discharged on nonsteroidal anti-inflammatory drugs (NSAIDs) (23.1 vs 4.8%, p = .025). Multivariable analysis demonstrated an increased risk of readmission for patients not treated with intravenous pulse methylprednisolone (IVMP) (OR = 17.5 (1.81–168.32) p = .013), and for those who required intravenous albumin assisted diuresis for hypervolemia (OR=6.25 (1.29–30.30) p = .022). Conclusion: In all, 17% of children hospitalized due to new onset lupus nephritis were readmitted within 30 days of discharge. Absence of IVMP and receiving intravenous albumin assisted diuresis during initial hospitalization increase the risk of early readmission in new onset pediatric lupus nephritis.